Application-based Simulations to Understand the Management Concepts of Electrical Load-shedding: A Case Study of the Electricity System on Offshore Platforms - Goeritno, Arief; Syamsudin, Tangtang; Azama, Irham Muhammad; Waluyo, Roy; Fitriani, Fitriani (Master Program in Mechanical Engineering, Gunadarma University, 2026)
This article describes the management concepts of electrical load-shedding in the electricity system of the offshore platforms environments for drilling to produce gases and oils. Stable and efficient electrical systems are essential for offshore platforms to ensure safety, productivity, and operational continuity. Load-shedding is a critical function that maintains the balance between power generation and demand during contingency events. This study employs an application-based simulation methodology to evaluate management strategies for electrical load-shedding in offshore electricity systems. Eight simulation scenarios assessed various operational conditions, including generator capacity, transformer performance, cable characteristics, and load prioritization. The results identify the feasibility and limitations of each scenario, illustrating the effects of different shedding strategies on power flow distribution, voltage stability, and system losses. The analysis shows that some configurations maintain stability margins, while others result in operational infeasibility due to voltage drops and overloading. The findings emphasize the necessity of structured load prioritization and the integration of automation using programmable logic controller (PLC)-assisted systems to improve system resilience. These results offer practical guidance for offshore operators, supporting enhanced planning and decision-making for reliable load-shedding strategies.